Pengembangan model pelatihan menembak yang ditargetkan untuk meningkatkan akurasi tembakan pada pemain sepak bola muda - Daulay, Basyaruddin; Silalahi, Christeven; Nababan, Oktonius Gabriel; Azzam, Muhammad; Nurkadri, Nurkadri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Repetitive drills with little target variation often reduce the shooting accuracy of youth players and limit their transfer to real match situations. This study aims to develop and test a goal-based shooting training model designed to improve shot-on-target probability among adolescent soccer players. A modified Borg and Gall Research and Development (R&D) framework was applied, condensing the original stages into four core phases needs analysis, expert validation, field trials, and effectiveness testing to ensure methodological efficiency and practical relevance. The research involved non-elite players aged 15–17 years and coaches from three football schools (SSBs): FC Siantar City, Parmo Jaya FC, and Putra Buana FC. Needs analysis indicated that most athletes demonstrated low shooting accuracy, and coaches reported that existing drills lacked target orientation and representative variation. Expert validation yielded high feasibility scores, with material experts rating the model at 91.25% and language experts at 87.50%. Practicality testing also showed excellent coach acceptability, ranging from 90.62% to 94.79%. Effectiveness testing revealed a substantial improvement in shooting accuracy after a four-week intervention, with mean scores increasing from 8.3 to 12.5 (Δ = 35.7%), confirming meaningful practical gains. The model incorporates goal-based target variability and representative learning design to provide structured visual feedback, thereby enhancing technical accuracy more effectively than generic repetition-based routines. Overall, the findings demonstrate that the developed model is valid, practical, and effective for non-elite U-15 to U-17 soccer training environments and may serve as an alternative program for improving finishing accuracy in youth football.